Perbaikan Tata Letak Mesin dan Material Handling di PT. X Menggunakan Systematic Layout Planning - Rosyita Firdaus; Anda Iviana Juniani; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
This research aims to redesign the factory layout of PT. X in order to minimize material handling distance. The company adheres to a job shop that demands greater system flexibility. Besides that one operator get a variety of tasks such as operating machinery, conducting quality control and doing material handling. This require the operator to move quickly so that the time can be used maximally for the machining process. The research results the layout engineering of machine and material handling using the Systematic Layout Planning (SLP) method. The re-layout procedure consists of three steps: analyzing the initial layout, designing the layout alternatives based on SLP, evaluating and selecting alternative layouts with a cost comparison technique. An efficiency improvement of material handling is obtained by alternative layout 1. The results showed a decrease in material handling costs (forklift) by 29.18% and a reduction of the total material handling costs up to 18.4% from the initial layout.